Multiplex Jeopardy: Dissonant Ties Promote Gender Bias in Workplace Social Networks - Brands, Raina A.; Kilduff, Martin (Academy of Management Review, 2025)
This paper develops new theory on how dissonant ties—work relationships characterized by positive and negative valence—shape gender inequality in organizational networks. We introduce the concept of multiplex jeopardy to explain how dissonant ties disproportionately harm women, due to their overlap with gender stereotypes. Specifically, we argue that like–disrespect ties reinforce perceptions of women as warm but incompetent, whereas dislike–respect ties reinforce perceptions of women as cold but competent, leading to both passive harm and active backlash. We further theorize that these effects extend beyond direct relationships to shape women’s experiences and outcomes through indirect gender bias. This bias distorts reputations, stifles information flow, limits career advancement, and contributes to structural inequality by reinforcing gendered network positions. We offer three theoretical contributions: (1) a novel lens on gendered outcomes in informal networks, (2) a social psychological account of how stereotypes become embedded in everyday work relationships, and (3) insight into how informal dynamics sustain gender inequality in organizations.